Adsorptive recovery of ethylene by CuCl loaded activated carbon via π-complexation - Xiaolong Zhou; Minchao Feng; Hui Niu; Yueqin Song; Chenglie Li; Dongwen Zhong (Adsorption Science & Technology)
Ethylene is recovered from ethylene/ethane mixture by adsorptive separation on CuCl 2 loaded activated carbon. When 36.7% of CuCl 2 were dispersed on activated carbon made from coconut shell (CSC) and calcined at 400℃ for some hours, a satisfactory adsorbent sample was prepared. The adsorption capacity of ethylene reached 23.55 mg/g and ethylene/ethane separation factor reached 7.6. Adsorbent characterization by various modern instruments demonstrated the reduction of CuCl 2 to provide Cu + cation on CSC, which is responsible to form π-complexation bonds for the adsorption of ethylene. Mechanism was discussed. Nature of related active centers was suggested.